Relational Capital and Connectedness in Adaptive Governance Processes: A Case Study of the Kafue Flats, Zambia. Issue 11 (2nd November 2021) - Chomba, Machaya J.; Hill, Trevor; Nkhata, Bimo A.
Abstract: The paper examines relational capital in form of trust and connectedness as key attributes of social interactions among social actors involved in adaptive governance processes. The research is a longitudinal case study of efforts for restoring the ecological integrity of the Kafue Flats for the period 1977–2004. The paper reveals low relational capital between local communities and Zambia Electricity Supply Corporation (ZESCO) due to poor information sharing and dialogue regarding the operations of the dams. In addition, negative connectedness is attributed to differences in the timing of water resource needs. On the other hand, high relational capital between ZESCO and commercial irrigation users due to the exchange of information and shared understanding of the resource system with positive connectedness is attributed to similarity in water resource needs in terms of timing and organizational capacity. In view of this, it is argued that adaptive governance requires collaborative relationships characterized by high relational capital and positive connectedness.